Composite positive electrode material and preparation method thereof, battery positive plate and all-solid-state battery

By covering the surface of the positive electrode material of all-solid lithium-ion batteries with nano-scale LLZCO and polymer-based solid electrolytes to form a composite positive electrode material, the problem of particle fragmentation and powderization of the positive electrode material during recycling is solved, and the strength of the material is improved and stability enhances battery safety.

CN119447269AActive Publication Date: 2025-02-14SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411737075.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

During the recycling process of all-solid lithium-ion batteries, problems such as the cathode material particles fragmentation and material powderization have caused the material capacity and circulation stability to decrease and brought safety hazards.

Method used

Using a composite positive electrode material, a core-shell structure is formed by covering the first cladding layer of nanoscale LLZCO and the second cladding layer of polymer-based solid electrolyte on the surface of the ternary positive electrode material.

Benefits of technology

The strength of the composite positive electrode material particles is improved, the structural integrity is protected, the lithium ion diffusion coefficient is enhanced, the charge transfer resistance is reduced, and the high-voltage decomposition reaction of the electrolyte is suppressed, which improves the structural stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447269A_ABST
    Figure CN119447269A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material and a preparation method thereof, a battery positive plate and an all-solid-state battery, the composite positive electrode material is used for the all-solid-state battery, and the composite positive electrode material comprises a core part of a ternary positive electrode material and a coating layer located on the surface of the core; the coating layer comprises a first coating layer core and a second coating layer, and the first coating layer is positioned between the core surface of the ternary positive electrode material and the second coating layer; the first coating layer is made of nanoscale LLZCO, and the second coating layer is made of polymer-based solid electrolyte; the first coating layer can improve the strength of the positive electrode particles, protect the structural integrity in the cyclic process, improve the diffusion coefficient of lithium ions and reduce the charge transfer resistance. And the second coating layer can inhibit the high-pressure decomposition reaction of the sulfide electrolyte, and the lower Young modulus can well buffer the volume deformation between positive electrode particles when ions are embedded and removed, so that the contact failure of a positive electrode-electrolyte interface is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of all-solid-state lithium-ion battery materials, and in particular to a composite positive electrode material and a preparation method thereof, a battery positive electrode sheet, and an all-solid-state battery. Background Art

[0002] Lithium batteries are one of the fastest growing batteries. However, as the market demand for lithium batteries increases, the safety of lithium batteries becomes increasingly prominent. Many spontaneous combustion accidents of mobile phones and cars are caused by a short circuit inside the battery that generates a lot of heat, leading to the decomposition of the internal electrolyte. At the same time, as people's requirements for the energy density of lithium-ion batteries are getting higher and higher, it is also a great challenge to the existing lithium-ion battery system.

[0003] From the perspective of the positive electrode, the traditional lithium iron phosphate positive electrode can no longer meet daily needs, and the nickel content of the ternary positive electrode material is also constantly increasing. However, with the increase in the nickel content of the ternary material, the cycle stability and high temperature stability of the material are decreasing. The phase change of the positive electrode material during the cycle causes the unit cell to shrink sharply, which brings about problems such as particle fragmentation and material pulverization, which not only affects the capacity and cycle stability of the material, but also brings a large number of gas production problems. In addition, when the positive electrode material is in a low lithium embedded state, the layered structure is prone to collapse, and oxygen is released at the same time, which brings more serious safety problems. Therefore, coating the electrode material is a necessary and effective means. However, the current commercial coating methods are relatively single, and the commonly used inorganic coating has poor lithium conductivity, so it cannot meet the needs of the next generation of lithium-ion batteries.

[0004] Therefore, there is an urgent need for a composite positive electrode material that can overcome the problems of positive electrode material particle fragmentation and material pulverization during the cycle and also improve the lithium ion diffusion coefficient. Summary of the invention

[0005] In order to solve the problems of positive electrode material particle fragmentation and material pulverization during the recycling of the above-mentioned background technology all-solid-state battery, the present invention provides the following technical solutions:

[0006] A first aspect of the present invention provides a composite cathode material for an all-solid-state battery, the composite cathode material comprising:

[0007] A core of a ternary cathode material and a coating layer located on the surface of the core;

[0008] The coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located between the core surface of the ternary positive electrode material and the second coating layer;

[0009] The first coating layer is nano-scale LLZCO, and the second coating layer is a polymer-based solid electrolyte.

[0010] Preferably, the nano-scale LLZCO ranges from 1 nm to 100 nm;

[0011] Preferably, the ternary positive electrode material is one of lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA); and / or.

[0012] Preferably, the preparation method of the nano-scale LLZCO is one of a sol-gel method, a hydrothermal synthesis method, a high-energy ball milling method and a co-precipitation method.

[0013] Preferably, the nano-LLZCO is prepared by mixing La2O3, ZrO2, Co2O3 and Li2CO3, calcining the mixture at high temperature into powder, and then ball-milling the powder into nano-LLZCO.

[0014] Preferably, the polymer-based solid electrolyte is one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO) and polyvinylidene chloride (PVDC).

[0015] Preferably, the mass ratio of the core portion to the first coating layer is greater than 20;

[0016] Preferably, the mass ratio of the second coating layer to the first coating layer is (1:1) to (10:1).

[0017] Preferably, the thickness of the first coating layer is 1 nm to 5 nm.

[0018] Preferably, the thickness of the second coating layer is 1 nm to 5 nm.

[0019] Preferably, the second coating layer is coated on the surface of the first coating layer by a wet chemical method.

[0020] The second aspect of the present invention provides a method for preparing the composite positive electrode material provided in the first aspect, comprising the following steps:

[0021] S1: The core part and the nano-LLZCO are ball-milled and mixed according to a mass ratio;

[0022] S2: calcining the material after ball milling in step S1 under an oxygen atmosphere to obtain a LLZCO primary coating material;

[0023] S3: dissolving the polymer-based solid electrolyte in a solvent to obtain a polymer-based solid electrolyte dispersion;

[0024] S4: adding the primary coating material prepared in step S2 to the dispersion in step S3 and stirring;

[0025] S5: Centrifugal drying to finally obtain a composite positive electrode material with a core-shell structure.

[0026] The third aspect of the present invention provides a battery positive electrode, using the composite positive electrode material of the first aspect, a first solid electrolyte, a conductive agent and a binder.

[0027] The fourth aspect of the present invention provides an all-solid-state battery using the positive electrode sheet, negative electrode sheet and second solid electrolyte proposed in the third aspect.

[0028] The beneficial effects of the present invention are:

[0029] (I) The first coating layer can improve the strength of the composite cathode material particles, protect the structural integrity during the cycle, and also improve the lithium ion diffusion coefficient and reduce the charge transfer resistance. The second coating layer can inhibit the high-pressure decomposition reaction of the sulfide electrolyte, and the lower Young's modulus can well buffer the volume deformation between the cathode particles during ion insertion and extraction, prevent the contact failure of the cathode-electrolyte interface, and improve the structural stability of the composite cathode material in the all-solid-state battery.

[0030] (ii) The second coating layer can fill the area of ​​the composite positive electrode material that the first coating layer of LLZCO fails to cover, making the surface coating layer of the composite positive electrode material more uniform, avoiding direct contact between the core and the electrolyte, and effectively inhibiting the high-voltage positive electrode from oxidizing the electrolyte. Secondly, the polymer is relatively soft and can fill the gap between the core and the electrolyte, which is beneficial to Li + conduction and reduce impedance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0032] Figure 1 This is a SEM image of the positive electrode surface of the all-solid-state battery after cycling in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0036] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0037] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0038] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0039] As the nickel content of ternary materials increases, the cycle stability and high-temperature stability of the materials are decreasing. The phase change of the positive electrode material during the cycle causes the unit cell to shrink sharply, which brings about problems such as particle fragmentation and material pulverization, which not only affects the capacity and cycle stability of the material, but also brings about a large number of gas production problems. In addition, when the positive electrode material is in a low lithium embedded state, the layered structure is prone to collapse, and oxygen is released at the same time, which brings about more serious safety problems. Therefore, coating the electrode material is a necessary and effective means. However, the current commercial coating methods are relatively single, and the commonly used inorganic coatings have poor lithium conductivity, and therefore cannot meet the needs of the next generation of lithium-ion batteries.

[0040] In order to solve the above technical problems, the present invention discloses a composite positive electrode material, a battery positive electrode, and an all-solid-state battery. The present invention coats a first coating layer of nano-scale LLZCO and a second coating layer of a polymer-based solid electrolyte on the surface of a ternary positive electrode material. The composite positive electrode material can be used in an all-solid-state battery to effectively improve the cycle performance of the battery.

[0041] The technical solution of the present invention is implemented as follows:

[0042] A first aspect of the present invention provides a composite cathode material for an all-solid-state battery, the composite cathode material comprising:

[0043] A core of a ternary cathode material and a coating layer located on the surface of the core;

[0044] The coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located between the core surface of the ternary positive electrode material and the second coating layer;

[0045] The first coating layer is nano-scale LLZCO, and the second coating layer is a polymer-based solid electrolyte.

[0046] Specifically, the second coating layer can fill the area of ​​the composite positive electrode material that is not covered by the LLZCO first coating layer, making the surface coating layer of the composite positive electrode material more uniform.

[0047] The first coating layer can improve the strength of the positive electrode particles, protect the structural integrity during the cycle, and can also increase the lithium ion diffusion coefficient and reduce the charge transfer resistance. The second coating layer can inhibit the high-pressure decomposition reaction of the sulfide electrolyte, and the lower Young's modulus can well buffer the volume deformation between the positive electrode particles during ion insertion and extraction, prevent the contact failure of the positive electrode-electrolyte interface, and improve the structural stability of the positive electrode composite material in the all-solid-state battery.

[0048] In one embodiment, the ternary positive electrode material is one of lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA); and / or.

[0049] In one embodiment, the preparation method of the nano-LLZCO is one of a sol-gel method, a hydrothermal synthesis method, a high-energy ball milling method and a co-precipitation method.

[0050] In one embodiment, the nano-LLZCO is prepared by mixing La2O3, ZrO2, Co2O3 and Li2CO3, calcining the mixture at high temperature into powder, and then ball-milling the powder into nano-LLZCO.

[0051] In one embodiment, the polymer-based solid electrolyte is one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO) and polyvinylidene chloride (PVDC).

[0052] In one embodiment, the mass ratio of the core portion to the first cladding layer is greater than 20;

[0053] In one embodiment, the mass ratio of the core portion to the first coating layer can be selected to be 25, 33, 50, 83, 100, 120, 200, 250, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.

[0054] In one embodiment, the mass ratio of the second coating layer to the first coating layer is (1:1) to (10:1).

[0055] In one embodiment, the mass ratio of the second coating layer to the first coating layer can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.

[0056] In one embodiment, the thickness of the first coating layer is 1 nm to 5 nm.

[0057] In one embodiment, the thickness of the first coating layer can be selected to be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.

[0058] In one embodiment, the thickness of the second coating layer is 1 nm to 5 nm.

[0059] In one embodiment, the thickness of the second coating layer can be selected to be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.

[0060] In one embodiment, the second coating layer is coated on the surface of the prefabricated material by a wet chemical method.

[0061] The second aspect of the present invention provides a method for preparing the composite positive electrode material provided in the first aspect, comprising the following steps:

[0062] S1: The core part and the nano-LLZCO are ball-milled and mixed according to a mass ratio;

[0063] S2: calcining the material after ball milling in step S1 under an oxygen atmosphere to obtain a LLZCO primary coating material;

[0064] S3: dissolving the polymer-based solid electrolyte in a solvent to obtain a polymer-based solid electrolyte dispersion;

[0065] S4: adding the primary coating material prepared in step S2 to the dispersion in step S3 and stirring;

[0066] S5: Centrifugal drying to finally obtain a composite positive electrode material with a core-shell structure.

[0067] In one embodiment, the preparation method of the composite positive electrode material, step S1 uses ball milling to wrap nano LLZCO particles on the surface of the positive electrode material, weighing 0.02-0.2g LLZCO nanoparticles and 5g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) positive electrode material is ball-milled and mixed, the ball-to-material ratio is (3-10):1, the ball-milling speed is 150rpm-300rpm, and the ball-milling time is 1h-6h; step S2 is to calcine the ball-milled material at 500℃-650℃ for 4h-10h under an oxygen atmosphere to obtain a LLZCO primary coating material.

[0068] In one embodiment, the preparation method of the composite positive electrode material, the mass of the LLZCO nanoparticles can be selected from 0.02g, 0.06g, 0.1g, 0.15g, 0.2g, etc., the ball-to-material ratio during ball milling can be selected from 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., the ball milling speed can be selected from 150rpm, 200rpm, 250rpm, 300rpm, etc., the ball milling time can be selected from 1h, 2h, 3h, 4h, 5h, 6h, etc., the calcination temperature can be selected from 500°C, 550°C, 600°C, 650°C, etc., and the calcination time can be selected from 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc. The above-listed numerical ratios are only examples, and the present invention does not impose any limitation on this.

[0069] In one embodiment, in the method for preparing the composite positive electrode material, step S3 uses a wet chemical method to coat the polymer-based solid electrolyte on the surface of the LLZCO primary coating material. Weigh 0.01 g to 0.25 g of a 50,000 gmol -1~200000g mol -1 The polymer-based solid electrolyte is dissolved in 5g to 20g of solvent, and ultrasonic stirring is performed for 10min to 30min each time to obtain a polymer-based solid electrolyte dispersion; step S4 adds the primary coating material prepared in step S2 to the dispersion of step S3, and ultrasonic stirring is performed for 10min to 30min each time; step S5 centrifuges at a speed of 2000rpm to 8000rpm for 5min to 10min, and the solid sample is dried at 60℃ to 100℃ for 6h to 18h to obtain a double-coated positive electrode material.

[0070] In one embodiment, the solvent is one of dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylpropionamide (DMF), N-methyl-2-pyrrolidone (NMPyr) and N-ethylpyrrolidone (NEP).

[0071] In one embodiment, in the method for preparing the composite positive electrode material, the mass of the polymer-based solid electrolyte in step S3 can be selected from 0.01g, 0.03g, 0.05g, 0.07g, 0.1g, 0.12g, 0.14g, 0.16g, 0.18g, 0.2g, 0.22g, 0.25g, etc., and the average molecular weight can be selected from 50000g·mol -1 、60000g·mol -1 , 70000g·mol -1 , 80000g·mol -1 , 90000g·mol -1 , 100000g·mol -1 、110000g·mol -1 , 120000g·mol -1 , 130000g·mol -1 , 140000g·mol -1 , 150000g·mol -1 , 160000g·mol -1 , 170000g·mol -1 , 180000g·mol -1 , 190000g·mol -1 , 200000g·mol -1etc., the solvent mass can be selected as 5g, 10g, 15g, 20g, etc., the ultrasonic stirring time can be selected as 10min, 15min, 20min, 25min, 30min, etc., the centrifugal speed can be selected as 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, etc., the centrifugal time can be selected as 5min, 6min, 7min, 8min, 9min, 10min, etc., the drying temperature can be selected as 60℃, 70℃, 80℃, 90℃, 100℃, etc., the drying time can be selected as 6h, 8h, 10h, 12h, 14h, 16h, 18h, etc. The above listed numerical ratios are only examples, and the present invention does not impose any limitation on this.

[0072] The third aspect of the present invention provides a battery positive electrode, using the composite positive electrode material of the first aspect, a first solid electrolyte, a conductive agent and a binder.

[0073] In one embodiment, the first solid electrolyte material is a sulfide solid electrolyte: Li6PS5X (LPSX, X = Cl, Br, I), Li 10 GeP2S 12 (LGPS) or more; and / or.

[0074] In one embodiment, the conductive material refers to one or more of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene.

[0075] In one embodiment, the binder material is one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), nitrile rubber (NBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA).

[0076] The fourth aspect of the present invention provides an all-solid-state battery using the positive electrode sheet, negative electrode sheet and second solid electrolyte proposed in the third aspect.

[0077] For example, the all-solid-state battery is manufactured according to the following preparation method:

[0078] Preparation of battery positive electrode: The composite positive electrode material obtained in the first aspect is evenly mixed with Li6PS5Cl solid electrolyte, conductive agent carbon nanofiber and binder PTFE in a mass ratio of 70:26:3:1, and then slurry coated on the positive electrode collector (aluminum foil), dried, rolled and cut to obtain the battery positive electrode.

[0079] Preparation of battery negative electrode: 95% negative electrode active material, 2% solid electrolyte, 2% conductive agent and 1% binder are mixed to form negative electrode slurry, which is then coated on the negative electrode current collector (copper foil), dried, rolled and cut to obtain negative electrode sheets. In the negative electrode active material, graphite: silicon oxygen = 80%: 20%.

[0080] Solid electrolyte layer preparation method: The solid electrolyte layer is composed of a second solid electrolyte and a binder (PTFE); the mass ratio of the two is 99:1.

[0081] In one embodiment, the second solid electrolyte material is a sulfide solid electrolyte: Li6PS5X (LPSX, X = Cl, Br, I), Li 10 GeP2S 12 (LGPS) or more; and / or.

[0082] Preparation of all-solid-state battery: The positive electrode, solid electrolyte layer and negative electrode are stacked and encapsulated in an aluminum-plastic film in sequence. After vacuum is applied to the aluminum-plastic film, it is sealed and the battery is isostatically pressed at 460MPa to obtain an all-solid-state lithium-ion battery.

[0083] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are all solid-state battery sample groups prepared by the same process.

[0084] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples record or perform the following tests: 0.1C first discharge specific capacity, 0.1C first coulombic efficiency, capacity retention rate after 100 cycles at 0.5C, capacity retention rate after 100 cycles at 1C, and ionic conductivity.

[0085] It should be noted that the embodiments of the present invention are not limited to these examples.

[0086] Example 1

[0087] 1. Li 7.5 LqCy 1.5 Co 0.5 O 12 Material preparation method:

[0088] 1) According to the ratio of each element in LLZCO, weigh the corresponding mass of La2O3, ZrO2, Co2O3 and Li2CO3.

[0089] 2) Mix the raw materials in a ball mill at a speed of 300 r / min -1 , ball milling time 12h.

[0090] 3) The mixture was sintered at 880°C for 8 h, and the calcined powder material was finally heated at 500 r / min. -1 The LLZCO nanomaterials were obtained by ball milling for 40 h.

[0091] 2. Preparation of composite cathode materials

[0092] 1) Weigh 0.1g Li 7.5 LqCy 1.5 Co 0.5 O 12 Nanoparticles, with 5g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) positive electrode material was ball-milled and mixed, with a ball-to-material ratio of 3:1, a rotation speed of 200 rpm, and a ball-milling time of 2 h.

[0093] 2) The ball-milled material was calcined at 550°C for 6 h in an oxygen atmosphere to obtain Li 7.5 LqCy 1.5 Co 0.5 O 12 The primary coating material has a first coating layer thickness of 2 nm.

[0094] 3) Weigh 0.2 g of an average molecular weight of 100,000 g mol -1 PEO was dissolved in 10g dimethylformamide (DMF) solution and ultrasonically stirred for 30min each to obtain a PEO dispersion; the primary coating material prepared above was added to the dispersion and ultrasonically stirred for 20min each, and then centrifuged and dried, and the thickness of the second coating layer was 2nm; finally, a core-shell structured double-coated positive electrode material, namely, a PEO@LLZCO-NCM811 composite positive electrode material, was obtained.

[0095] 2. Preparation of battery positive electrode

[0096] The composite positive electrode material obtained in the first step is evenly mixed with Li6PS5Cl solid electrolyte, conductive agent carbon nanofiber and binder PTFE in a mass ratio of 70:26:3:1, and then slurry coated on the positive electrode collector (aluminum foil), dried, rolled and cut to obtain the battery positive electrode.

[0097] 3. Preparation of battery negative electrode

[0098] 95% of negative electrode active material, 2% of solid electrolyte Li6PS5Cl, 2% of conductive carbon black and 1% of binder PAA are mixed to form negative electrode slurry, which is then coated on the negative electrode current collector (copper foil), dried, rolled and cut to obtain negative electrode sheets. In the negative electrode active material, graphite: silicon oxygen = 80%: 20%.

[0099] 4. Solid Electrolyte Layer Preparation Method

[0100] The solid electrolyte layer is composed of a second solid electrolyte Li6PS5Cl and a binder PTFE; the mass ratio of the two is 99:1.

[0101] 5. All-solid-state battery preparation

[0102] The positive electrode, solid electrolyte layer and negative electrode of the battery are stacked and packaged in an aluminum-plastic film in sequence. After vacuum is applied to the aluminum-plastic film, it is sealed and the battery is isostatically pressed at 460 MPa to obtain an all-solid-state lithium-ion battery.

[0103] Example 2

[0104] Example 1 provides a composite positive electrode material, a battery positive electrode and an all-solid-state battery, which are the same as the coating material and preparation method used in Example 1, and the only difference from Example 1 is that the mass of LLZCO is 0.02g.

[0105] Example 3

[0106] Example 1 provides a composite positive electrode material, a battery positive electrode and an all-solid-state battery, which are the same as the coating material and preparation method used in Example 1, and the only difference from Example 1 is that the mass of LLZCO is 0.06g.

[0107] Example 4

[0108] Example 1 provides a composite positive electrode material, a battery positive electrode and an all-solid-state battery, which are the same as the coating material and preparation method used in Example 1, and the only difference from Example 1 is that the mass of LLZCO is 0.15g.

[0109] Example 5

[0110] Example 1 provides a composite positive electrode material, a battery positive electrode and an all-solid-state battery, which are the same as the coating material and preparation method used in Example 1, and the only difference from Example 1 is that the mass of LLZCO is 0.2g.

[0111] Comparative Example 1

[0112] The coating material and preparation method used in Example 1 are the same, and the difference from Example 1 is that neither LLZCO material nor PEO material is coated.

[0113] Comparative Example 2

[0114] The coating material and preparation method used in Example 1 are the same, and the difference from Example 1 is that only LLZCO is coated, and the material mass is 0.2 g.

[0115] Comparative Example 3

[0116] The coating material and preparation method used in Example 1 are the same, and the difference from Example 1 is that only PEO material is coated, and the mass of PEO material is 0.2g.

[0117] Comparative Example 4

[0118] The coating material and preparation method used in Example 1 are the same, and the difference from Example 1 is that the mass of the coated LLZCO material is 0.3 g, and the mass of the coated PEO material is 0.3 g.

[0119] The positive electrode materials obtained in Examples 1-5 and Comparative Examples 1-4 were prepared into battery positive electrodes, and the battery positive electrodes were used in all-solid-state batteries, and their performance was tested.

[0120] The composite positive electrode materials prepared in the above Examples 1 to 5 and Comparative Examples 1 to 3 were used to prepare all-solid-state batteries, and the performance of the all-solid-state batteries was tested. The test results are shown in Table 1 below:

[0121] First discharge capacity test:

[0122] At room temperature (25°C), the fully charged battery was discharged at a constant current of 0.1C to a cut-off voltage of 2.5V to obtain the first discharge capacity.

[0123] First Coulombic efficiency:

[0124] The first discharge specific capacity / first charge specific capacity when charging and discharging at 0.1C current.

[0125] The first coulombic efficiency refers to the coulombic efficiency during the first charge and discharge process of the battery. The coulombic efficiency is the efficiency of the charge in the battery during the charge and discharge process, expressed as: coulombic efficiency = (discharge capacity / charge capacity) × 100%.

[0126] Cyclic battery capacity retention rate:

[0127] At a temperature of 45°C, charge with a current of 0.5C and 1C respectively to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, stand for 0.5h, then discharge with a current of 0.5C and 1C respectively to a cut-off voltage of 2.5V, stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 100 charge and discharge cycles.

[0128] Ionic conductivity:

[0129] The AC impedance of the sample is measured, and then the ionic conductivity of the sample is calculated by the formula σ=L / (R×S), where L is the thickness, R is the impedance, and S is the cross-sectional area.

[0130] The performance test results are shown in Table 1.

[0131] Table 1: Comparison of material performance tests in Examples 1-5 and Comparative Examples 1-4

[0132]

[0133] According to the above table, by comparing Examples 1 to 5 with Comparative Examples 1 to 4, the present invention provides a composite positive electrode material, wherein Li is coated on the surface of the ternary positive electrode material. 7.5 Ln3Z 1.5 Co 0.5 O 12 (first coating layer, close to the positive electrode) and polymer layer (second coating layer), the first coating layer can improve the strength of the composite positive electrode material particles and protect the structural integrity during the cycle; the second coating layer can inhibit the high-pressure decomposition reaction of the sulfide electrolyte, and the lower Young's modulus can well buffer the volume deformation between the positive electrode particles during ion embedding and extraction, prevent the contact failure of the positive electrode-electrolyte interface, and improve the structural stability of the composite positive electrode material in the all-solid-state battery. The second coating layer can fill the area of ​​the composite positive electrode material that the LLZCO first coating layer failed to wrap, making the surface coating layer of the composite positive electrode material more uniform, avoiding direct contact between the core and the electrolyte, and effectively inhibiting the high-voltage positive electrode from oxidizing the electrolyte. Secondly, the polymer is relatively soft and can fill the gap between the core and the electrolyte, which is beneficial to Li + conduction and improve ionic conductivity.

[0134] In Examples 1 to 5, the PEO coating amount of the second coating layer is kept at 0.2g. As the LLZCO coating amount increases, the 0.1C first discharge specific capacity, the 0.1C first coulombic efficiency, the capacity retention rate after 100 cycles at 0.5C, the capacity retention rate after 100 cycles at 1C, and the ionic conductivity are all in a trend of first increasing and then decreasing. When the LLZCO coating amount is 0.1g, that is, the mass ratio of PEO to LLZCO is 2:1, the battery performance reaches a peak. Therefore, the double-coating material can improve the first efficiency, cycle performance, and ion conductivity of the battery.

[0135] Comparing Example 1 with Comparative Examples 1 to 4, when neither LLZCO material nor PEO material is coated, the first efficiency, cycle performance and ion conductivity reach the lowest. From Comparative Example 2, it can be seen that when only LLZCO and only PEO are coated, the overall performance of the battery is slightly improved, while when the coating amount of the two coating materials is excessive, the overall performance of the battery will decrease.

[0136] Figure 1 This is a SEM image of the positive electrode of the all-solid-state battery after cycling in Example 1. It can be seen that the positive electrode particles are relatively intact after cycling, indicating good contact with the electrolyte.

[0137] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite positive electrode material, characterized in that: The composite positive electrode material comprises: A core of a ternary cathode material and a coating layer located on the surface of the core; The coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located between the core surface of the ternary positive electrode material and the second coating layer; The first coating layer is nano-scale LLZCO, and the second coating layer is a polymer-based solid electrolyte.

2. The composite positive electrode material according to claim 1, characterized in that The polymer-based solid electrolyte is one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO) and polyvinylidene chloride (PVDC).

3. The composite positive electrode material according to claim 1, characterized in that The mass ratio of the core portion to the first coating layer is greater than 20.

4. The composite positive electrode material according to claim 1, characterized in that The mass ratio of the second coating layer to the first coating layer is (1:1) to (10:1).

5. The composite positive electrode material according to claim 1, characterized in that The thickness of the first coating layer is 1 nm to 5 nm.

6. The composite positive electrode material according to claim 1, characterized in that The thickness of the second coating layer is 1 nm to 5 nm.

7. The composite positive electrode material according to claim 1, characterized in that The second coating layer is coated on the surface of the first coating layer by a wet chemical method.

8. A method for preparing a composite positive electrode material, characterized in that: The steps include: S1: The core part and the nano-LLZCO are ball-milled and mixed according to a mass ratio; S2: calcining the material after ball milling in step S1 under an oxygen atmosphere to obtain a LLZCO primary coating material; S3: dissolving the polymer-based solid electrolyte in a solvent to obtain a polymer-based solid electrolyte dispersion; S4: adding the primary coating material prepared in step S2 to the dispersion in step S3 and stirring; S5: Centrifugal drying to finally obtain a composite positive electrode material with a core-shell structure.

9. A positive electrode sheet for a battery, characterized in that: The method comprises the composite positive electrode material as claimed in any one of claims 1 to 8, a first solid electrolyte, a conductive agent and a binder.

10. An all-solid-state battery, characterized in that: It comprises the positive electrode sheet, the negative electrode sheet and the second solid electrolyte as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium battery composite positive electrode material and preparation method thereof

    CN112310354A

  • Double-layer coated positive electrode composite material as well as preparation method and application thereof

    CN114824227A

  • Lithium ion battery composite positive electrode material and preparation method thereof

    CN115588733A

  • Double-coated positive electrode material, preparation method thereof and all-solid-state battery

    CN118572085A

  • Composite solid electrolyte material for battery negative electrode, negative electrode plate and all-solid-state lithium battery

    WO2022194219A1